Assessing Sultan Qaboos University’s Distance Learning Experience in Using Moodle Platform in Light of Emerging Coronavirus Pandemic from the Faculty Members' Point of View - Shahat, Mohamed; Al-amri, Mohammed (Dirasat: Educational Sciences, 2022)
Objectives: This study aims to assess Sultan Qaboos University's distance learning experience in using Moodle platform in light of emerging Coronavirus Pandemic from the faculty members' point of view. Method: A descriptive-analytical approach was used. A three-scale assessment instrument has been developed. Results: The results revealed medium effectiveness of the distance learning experience from the faculty members' point of view. It also found statistically significant differences between the faculty members' views regarding the effect of gender, whereas there was no statistically significant effect regarding the teaching experience. Conclusions: The study recommends the need for holding training programs and workshops to raise awareness of the technological culture, employing e-learning management systems, and designing e-courses.